SISTEM INFORMASI QUICK RESPONSE DAN PENGADUAN MASYARAKAT DI KANTOR KECAMATAN KOTA UTARA - Siti Fauziah Mohamad; Rampi Yusuf; Alfian Zakaria (Gorontalo State University, 2022)
Public complaints are a form of community participation to play a role in building the environment as well as a form of monitoring the performance of government agencies. Currently, the North City District Office does not yet have a public complaint service or system. So it is necessary to have a Public Complaints Information System to submit public complaints that are intended specifically for the North City District government and the application responds quickly to complaints, suggestions, a place to accommodate aspirations, first aid for humanitarian and emergency communities. The design used in this research is the Prototype method. This research produces a Quick Response and Community Complaints Information System to make it easier for the public to submit complaints which will be addressed specifically to the North City District government and can speed up the complaint time in real time because it is based on a Progressive Web App (PWA) that can be read by sub-district staff and forwarded. to the sub-district head for the complaint process.Keywords: Complaints, PWA, Prototype.